2012
DOI: 10.4074/s0003503312003053
|View full text |Cite
|
Sign up to set email alerts
|

Le sexisme bienveillant comme processus de maintien des inégalités sociales entre les genres

Abstract: 2Fonds National de la Recherche Scientifique RÉSUMÉ L'idée que le sexisme puisse s'exprimer sous forme de bienveillance peut paraître surprenante. En effet, la représentation que nous avons habituellement d'une personne sexiste est celle d'un homme aux attitudes clairement hostiles à l'égard des femmes. Le but de cette revue de littérature est de mettre en évidence une forme plus subtile de sexisme, le sexisme bienveillant, qui renvoie à des attitudes sexistes subjectivement positives, teintées de galanterie e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…According to the system justification perspective, stereotypes legitimize status inequalities between men and women by assigning stereotypical characteristics to men which are linked to high social status. On the other hand, characteristics stereotypically assigned to women are linked to lower social status but more positive social perceptions (Jost & Banaji, 1994;Rudman et al, 2012b).This idea is also reflected in the results of research on benevolent sexism (Glick & Fiske, 2001;Sarlet & Dardenne, 2012), which shows that one way through which the gender hierarchy is preserved is by perceiving women (and feminine stereotypes) positively but with no real power and as ultimately inferior to men (and masculine stereotypes). This was precisely the case in our study, in which we found that in general, the feminine targets were viewed more positively than masculine targets, but at the same time were viewed as having lower power and influence.…”
Section: Stereotypes and System Justification Theorymentioning
confidence: 93%
“…According to the system justification perspective, stereotypes legitimize status inequalities between men and women by assigning stereotypical characteristics to men which are linked to high social status. On the other hand, characteristics stereotypically assigned to women are linked to lower social status but more positive social perceptions (Jost & Banaji, 1994;Rudman et al, 2012b).This idea is also reflected in the results of research on benevolent sexism (Glick & Fiske, 2001;Sarlet & Dardenne, 2012), which shows that one way through which the gender hierarchy is preserved is by perceiving women (and feminine stereotypes) positively but with no real power and as ultimately inferior to men (and masculine stereotypes). This was precisely the case in our study, in which we found that in general, the feminine targets were viewed more positively than masculine targets, but at the same time were viewed as having lower power and influence.…”
Section: Stereotypes and System Justification Theorymentioning
confidence: 93%
“…Les stéréotypes portant sur les rôles respectifs à adopter sur la base du genre limiteraient les projections de carrière (Gray et O'Brien, 2007). En vertu de la différenciation complémentaire de genre caractérisant le sexisme bienveillant, les employées sont davantage protégées et sont confrontées à des situations de travail moins difficiles, dans lesquelles les défis sont moins stimulants (King et al, 2010 ;Sarlet et Dardenne, 2012). Elles sont victimes du stéréotype d'incompétence, en lien avec la conception chaleureuse des femmes diminuant leur dimension agentique (Rivera, 2020).…”
Section: Projections De Carrièreunclassified
“…Différentes théories portent sur le sexisme, dont la théorie du sexisme ambivalent proposée par Glick et Fiske (1996). Celle-ci postule qu'il existe deux types de sexisme, complémentaires l'un de l'autre : le sexisme hostile, considéré comme traditionnel, et le sexisme bienveillant, forme plus moderne (Sarlet et Dardenne, 2012). Dans le cadre de cette étude, nous nous concentrerons sur cette dernière forme et étudierons ses préjudices dans la sphère professionnelle.…”
Section: Introductionunclassified
See 2 more Smart Citations